An in vitro pilot study on the dimensional stability of shellac trial denture bases used in the U.P. College of Dentistry - Guevarra, Agnes Elsa R.; Maranon, Marie Joanne Susana R.; Magtanong, Danilo (Adviser).
Clinicians time and again complain about the instability of shellac trial denture bases but do they have basis for their claims? The purpose of this study is to establish if there is a significant dimensional change in the shellac trial denture bases in vitro. One hundred maxillary samples were made using a mold. These were then immersed in water at 37°C ± 1°C at different time intervals. Using the t test, results showed that there is a significant change in the material even at the initial time of 7 minutes.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Trial denture base (TDB).